Diagnostic and evaluative efficiency of 68Ga-FAPI-04 in skeletal muscle injury - Yiqun Wang; La Li; Hongde Wang; Jin Cheng; Cancan Du; Luzheng Xu; Yifei Fan; Xiaoqing Hu; Yu Yin; Ruimin Wang; Yingfang Ao (EJNMMI Research, 2024)
Abstract Background Skeletal muscles are vital for daily function, yet assessing their injuries remain challenging. We aimed to elucidate the effectiveness of 68Ga-FAPI-04 in evaluating skeletal muscle remodeling. Results C2C12 cells were subjected to graded H2O2 stimulation in vitro, revealing an initial rise and subsequent decline in fibroblast activation protein (FAP) expression as H2O2 concentration increased. In vivo, a murine triceps surae injury model was created using various solutions to simulate normal repair, mild repair failure, and severe repair failure. Assessments were conducted on days 1, 3, 7, and 14 using PET, MRI, and ultrasound. With 68Ga-FAPI-04, the normal and mild repair failure groups showed significantly higher SUVmax and T/B ratios on day 1 compared to the severe repair failure group. These values gradually decreased in the normal repair group, becoming negligible after day 7. MRI results for the normal repair group showed low to moderate signal intensity by day 7. A clinical study retrospectively evaluated post-hip arthroplasty patient images at intervals of 1 month, 2–3 months, 5–6 months, and over 7 months. In these patients, 18F-FDG SUVmax and volume remained relatively stable over time, while 68Ga-FAPI-04 SUVmax initially increased, then decreased, with a consistent reduction in volume. Conclusion In skeletal muscle injuries, FAP demonstrates a distinctive mechanism of action, and 68Ga-FAPI-04, in comparison to other tests, more precisely captures alterations in lesion site uptake intensity and volume. Trial registration Trial registration: ChiCTR2000041204. Registered 22 December 2020, https://www.chictr.org.cn/showproj.html?proj=66211